Ranula in an adult case series - Chavan, Shahaji; Kshirsagar, Vinayak; Bendre, Mahendra; Ambre, Sagar Ramesh; Banik, Rahul; Tripathi, Nishant; Sharma, Vishal (International Surgery Journal, 2017)
The ranula is a cyst like mass arising from sublingual gland. It originates from extravasation of mucus from sublingual gland. Ranula can be simple and plunging. The name came from latin word means frog. The ranula can be seen in intraoral and it affects the submandibular space and adjacent structure in the neck. This paper reviews case series of two case of ranula one in floor of mouth and one in the floor and affecting the submandibular space plunging ranula; both case been successfully treated marsupialization were done in first case and excision of the sublingual gland were done in second case. No complication was observed during intraoperative and postoperative period and both patients are in follow up there is no recurrence in 1 year period till now.